Pengaruh Model Joyful Learning dengan Media Power Point Interaktif terhadap Hasil Belajar Siswa Kelas V SD Negeri 193 Pekanbaru - Yulidaspa, Selpade; Mustika, Dea (Lembaga Yasin AlSys, 2023)
The purpose of this study was to determine the effect of the joyful learning model with interactive power point media on the learning outcomes of fifth grade students at SD Negeri 193 Pekanbaru. This study used a quasi-experimental type with nonequivalent control group design. The research sample consisted of 2 classes using the Cluster Random Sampling technique. The sample in this study is the VB class as the experimental class and the VA class as the control class. The hypothesis test in this study uses the t-test at a significance level of 5% with the calculation t_count 6.73 > t_table -1.67 this means t_count > t_table which means that H_0 is rejected and H_1 is accepted. Based on these results, it can be concluded that there is an influence of the joyful learning model with interactive power point media on the learning outcomes of fifth grade students at SD Negeri 193 Pekanbaru.